Evektivitas variasi latihan stepping zig-zag kick dan elastis kick terhadap kecepatan tendangan mawashi geri pada atlet karate kumite jonggat prestasi tahun 2022 - Putri AuliaSubakti; Elya Wibawa Syarifoeddin; Supriadin (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2023)
Based on observations, the speed of athletes’ kicks is still relatively low, resulting in less accurateexecution of the mawashi geri kick during matches. This study examines the effects of stepping zig-zag kick training and elastic kick training on the performance of the mawashi geri kick. The purpose of this study is to determine the effect of stepping zig-zag kick training and elastic kick training on mawashi geri kicking performance. The research method used is an experimental method with a two-group pretest and posttest design. The sample consisted of 20 participants. The research instrument used was a kick speed measurement test. The results of the study showed an increase in kick speed, where the stepping zig-zag kick training obtained a t-value of 8.251 > 1.833, while the elastic kick training obtained a t-value of 9.701 > 1.833. The results also indicated that the improvement from stepping zig-zag kick training had a greater mean difference compared to elastic kick training.